Amino Acid Trafficking and Skeletal Muscle Protein Synthesis: A Case of Supply and Demand - White, James P. (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle protein synthesis is a highly complex process, influenced by nutritional status, mechanical stimuli, repair programs, hormones and growth factors. The molecular aspects of protein synthesis are centered around the mTORC1 complex. However, the intricacies of mTORC1 regulation, both up and downstream, have expanded overtime. Moreover, the plastic nature of skeletal muscle makes it a unique tissue, having to coordinate between temporal changes in myofiber metabolism and hypertrophy/atrophy stimuli within a tissue with considerable protein content. Skeletal muscle manages the push and pull between anabolic and catabolic pathways through key regulatory proteins to promote energy production in times of nutrient deprivation or activate anabolic pathways in times of nutrient availability and anabolic stimuli. Branched-chain amino acids (BCAAs) can be used for both energy production and signaling to induce protein synthesis. The metabolism of BCAAs occur in tandem with energetic and anabolic processes, converging at several points along their respective pathways. The fate of intramuscular BCAAs adds another layer of regulation, which has consequences to promote or inhibit muscle fiber protein anabolism. This review will outline the general mechanisms of muscle protein synthesis and describe how metabolic pathways can regulate this process. Lastly, we will discuss how BCAA availability and demand coordinate with synthesis mechanisms and identify key factors involved in intramuscular BCAA trafficking.